The hidden ethical element of nursing care rationing - Andreou, Panayiota; Vryonides, Stavros; Papastavrou, Evridiki (My University, 2014)
Objective: To explore nurses’ experiences and perceptions about prioritizations, omissions, and rationing of bedside nursing care. Methods: A total of 23 nurses participated in four focus groups. The interviews were based on a semi-structured interview guide; data were analyzed using a thematic analysis approach. Findings: Four themes were developed based on the data: (a) priorities in the delivery of care; (b) professional roles, responsibilities, and role conflicts; (c) environmental factors influencing care omissions; and (d) perceived outcomes of rationing. Discussion: The delivery of nursing care is framed by the biomedical ethos and inter-professional role conflict while the standards of basic care are jeopardized. Organizational and environmental factors appear to exert significant influence on prioritization. Failure to carry out necessary nursing tasks may lead to adverse patient outcomes, role conflict, and an ethical burden on nurses. Conclusion: There is a need for further exploration and possible redesign of the nursing role, scope, and responsibilities, as well as addressing the arising ethical issues of rationing in nursing care.
Keywords: Ethics; Focus groups; Omissions; Quality of healthcare; rationing